'Japan, the West and the Whaling Issue: Understanding the Japanese Side' - Catalinac, Amy; Chan, Gerald (Japan Forum, 2005)
This article examines the current dispute over whaling from the perspective of Japan, a country that is fiercely protective of its right to whale. It outlines the key role played by transnational environmental actors in defining and instituting an international norm of anti-whaling, symbolized in the passage of the moratorium on commercial whaling in 1982. This signalled a rejection of previously held attitudes towards the use of whales as natural resources and the embracing of a protectionist, hands-off approach. Support for this new stance however was not forthcoming from pro-whaling states Japan, Norway and Iceland. By analysing Japan's original objection to the moratorium, its later compliance and its commitment to the resumption of limited commercial whaling, this article outlines the principles that underpin Japan's whaling policy. While the Japanese government views the whaling dispute as a threat to resource security and also a danger to inter-state respect for differences in custom and cuisine, the need to be perceived as a responsible member of international society exercises a major influence on the formation of Japan's whaling policy, conditioning its rule compliance and prohibiting the independent action pursued by other pro-whaling states. Recent developments in the whaling dispute, however, may be enough to dislodge Japan's commitment to the moratorium, which would impact upon the legitimacy of the International Whaling Commission itself.
EPrint Processing Status: DRO Team waiting for author to provide full text
Keywords: Centre for Contemporary Chinese Studies; Japanese whaling; International norms; Rule compliance; Environmental movements; International legitimacy.